Effect of dexamethasone therapy in Crimean-Congo hemorrhagic fever in Giresun: An analytical study - Sinan Çetin; Ahmet Melih Şahin; Emrullah Ataş; Emsal Aydın; İlknur Şenel; Meltem Arzu Yetkin (Journal of Vector Borne Diseases)
Background & objectives: Crimean-Congo hemorrhagic fever (CCHF) is a zoonotic disease and significant health concern particularly in endemic regions. We aimed to evaluate the efficacy in dexamethasone treatment on clinical outcomes in CCHF patients. Methods: We included adult patients diagnosed with CCHF and those whose platelet count dropped to 70,000/mm3 or lower. The efficacy of dexamethasone on clinical outcomes was evaluated. It was a retrospective analytical study. Results: All 55 patients received standard supportive treatment, and none of them received ribavirin therapy. It was observed that 23 (41.8%) patients were treated with dexamethasone. No significant differences were observed between patients treated with dexamethasone and without, regarding factors such as bleeding incidents during hospitalization, the need for blood product transfusions, thrombocyte recovery status, intensive care unit admission, and in-hospital mortality. In-hospital mortality was observed in two patients (3.6%). Interpretation & conclusion: Our study found that dexamethasone treatment did not lead to a significant improvement in the clinical outcomes for CCHF patients.